3D MicroCT spatial and temporal characterization of thoracic aorta perivascular adipose tissue and plaque volumes in the ApoE-/- mouse model. (3rd July 2018) - Faight, Erin; Verdelis, Kostas; Ahearn, Joseph M.; Shields, Kelly J.
ABSTRACT: Perivascular adipose tissue (PVAT) influences vascular function and pathology. We present a protocol using micro-computed tomography (microCT), a novel imaging technique typically used for hard biological tissue, to characterize the temporal and spatial development of aorta PVAT and luminal plaque soft tissue. Apolipoprotein E deficient (ApoE) and C57Bl/6J (control) mice were fed a high fat western diet up to 30 weeks. 3D microCT reconstructions were used to quantify: 1) vascular wall volume, a surrogate measure of remodeling, was greater in ApoE, 2) aorta PVAT volume was reduced in ApoE, 3) plaque volumes increased over time in ApoE, 4) plaque development co-localized with luminal ostia, origins of branching arteries, which traveled through areas of greatest PVAT volume, 5) qualitatively, the same arteries showed evidence of increased tortuosity in ApoE. This study reflects the potential of microCT analyses to assess vascular wall, PVAT and arterial trajectory modifications in relevant animal models. Abbreviations : PVAT: perivascular adipose tissue; ApoE: apolipoprotein E deficient mouse strain; Control: C57Bl/6J mouse strain; PTA: 0.3% phosphotungstic acid; microCT: micro-computed tomography; CV: cardiovascular; CVD: cardiovascular disease; IQR: interquartile range; PPARγ: peroxisome proliferator activated receptor – gamma; VV: vasa vasorum; 3D: three dimensional